2021
DOI: 10.3389/fpsyg.2021.655151
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Health in Patients on or at Risk of Sick Leave Due to Depression and Anxiety: Validity of the EQ-5D

Abstract: Objectives: The EQ-5D is a generic, self-report measure of health that is increasingly used in clinical settings, including mental health. The EQ-5D captures health using five dimensions: Mobility, Self-care, Usual activities, Pain/discomfort, and Anxiety/Depression. The validity of the EQ-5D is previously unexplored in patients on or at risk of sick leave due to depression and anxiety. The study’s aim was to examine its validity in this group of patients.Methods: Baseline data were collected from self-report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
3
3
0
Order By: Relevance
“…We found no association between age and HRQoL, which is in line with some previous research [ 16 , 30 ]. However, older age has also been related to lower HRQoL in physical aspects, and lower age has been related to mental problems [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found no association between age and HRQoL, which is in line with some previous research [ 16 , 30 ]. However, older age has also been related to lower HRQoL in physical aspects, and lower age has been related to mental problems [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…The second objective was to explore the relationship between different patient characteristics and HRQoL represented by EQ-5D values and VAS. Sick leave and being unemployed were associated with lower HRQoL, which is in accordance with previous findings [ 12 , 17 , 30 ]. Due to the cross-sectional data, we cannot infer any causal direction of this relationship, as being away from work may cause low HRQoL and vice versa.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A recent review evaluated the properties of the newer five-level version of the EQ-5D, the EQ-5D-5L, across multiple patient groups [11]. These and other studies of patients with mental health problems have shown moderate to good correlation between condition-specific measures and the EQ-5D-5L in crosssectional designs [11][12][13][14][15]. These studies did not include data on responsiveness [11].…”
Section: Introductionmentioning
confidence: 99%